Plant based diet and cardio-metabolic disease - Justyna Dąbrowska; Magdalena Wójcik; Joanna Borowik; Kinga Kuśmierczuk; Halina Pieciewicz-Szczęsna (Kazimierz Wielki University, 2020)
Introduction: Modern lifestyle, especially diet have a great impact on health. The number of people suffering from conditions related to lifestyle is growing rapidly. Illnesses related to lifestyle, specifically to diet are large health and economic burdens, which makes them the leading priorities of our time. Coronary heart disease (CHD), stroke, type 2 diabetes, and obesity are some of cardio-metabolic diseases related to diet.  Plant-based diets are dietary patterns in which  a high intake of plant food is emphasized  and the intake of animal products is limited. Plant based diet was associated with decreased risk of cardio-metabolic disease. The aim of the study: The purpose of this systemic review was to collect and analyse current data of plant based diet and its effect on health. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed and Google Scholar database was carried out using the following keywords: plant based diet, vegetarian diet, cardiovascular disease, type 2 diabetes, hypercholesterolemia. Description of the state of knowledge: Red meat and, especially processed meat, is source of cholesterol, saturated fatty acids, and sodium, which makes it a risk factors for metabolic disorders.  Healthy plant based diet can positively affect cardiovascular health in many ways. High fiber content makes those diets  low in energy density, flavonoids that are present in fruits and vegetables and also high content of antioxidants. Plant based diet was also shown to be helpful in reducing weight. Summary: Many risk factors of cardio-metabolic disease are related to our lifestyle and dietary choices . Changes towards plant based diet can be beneficial for our health in many ways. Healthy plant based diet should be considered as a nonpharmaceutical approach to prevent and treat cardio-metabolic diseases.